Type 2 diabetes, chronic kidney disease and major cardiovascular events in patients with established coronary artery disease. (14th October 2021) - Sprenger, L; Vonbank, A; Larcher, B; Mader, A; Maechler, M; Mutschlechner, B; Benda, M; Leiherer, A; Muendlein, A; Drexel, H; Saely, C H
Abstract:  : Both type 2 diabetes (T2DM) and chronic kidney disease (CKD) confer a high risk of cardiovascular disease (CVD), and these conditions frequently coincide. The purpose of this study was to investigate the single and joint effects of T2DM and CKD on major cardiovascular events (MACE) in a high-risk population of patients with established coronary artery disease (CAD). We prospectively investigated 1460 patients with angiographically proven CAD over 10.4±4.8 years, of whom 454 (30.8%) had T2DM and 251 (17.1%) had CKD. MACE occurred more frequently in T2DM patients than in non-diabetic subjects (40.4% vs 28.7%, p<0.001) and in patients with CKD (eGFR <60ml/min/1.73m 2 ) than in those with an eGRF ≥60ml/min/1.73m 2 (51.6% vs 28.3%, p<0.001). When both, T2DM and CKD were considered, 863 subjects had neither T2DM nor CKD, 346 had T2DM but not CKD, 148 did not have diabetes but had CKD, and 103 had both T2DM and CKD. When compared with the incidence of MACE among patients with neither T2DM nor CKD (25.3%), MACE occurred more frequently in patients with T2DM who did not have CKD (35.8%; p<0.001) as well as in non-diabetic patients with CKD (47.6%; p<0.001) and occurred most freuently in patients with both, T2DM and CKD (57.4%; p<0.001), in whom the incidence of MACE was higher than in those with T2DM but not CKD (p<0.001) or those without T2DM but with CKD (p=0.025); the incidence of MACE was higher in non-diabetic CKD patients than in T2DM patients who did not have CKD (p=0.041). In Cox regression analysis, T2DM (HR=1.46 [1.20–1.78]; p<0.001) and CKD (HR=1.81 [1.45–2.27]; p<0.001) were mutually independent predictors of MACE after multivariate adjustment. We conclude that T2DM and CKD are mutually independent risk factors for MACE in patients with established CAD. CAD patients with both CKD and T2DM are an extremely high risk for MACE. FUNDunding Acknowledgement: Type of funding sources: None.